2015
DOI: 10.1371/journal.pone.0116783
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Requirements of PLK1 during Mouse Oocyte Maturation

Abstract: Polo-like kinase 1 (PLK1) orchestrates multiple events of cell division. Although PLK1 function has been intensively studied in centriole-containing and rapidly cycling somatic cells, much less is known about its function in the meiotic divisions of mammalian oocytes, which arrest for a long period of time in prophase before meiotic resumption and lack centrioles for spindle assembly. Here, using specific small molecule inhibition combined with live mouse oocyte imaging, we comprehensively characterize meiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 77 publications
9
83
1
Order By: Relevance
“…This localization pattern was similar to that of the proteins involved in spindle formation, e.g. MDK28, PLK12930, Septin131, BARC132 and cep5533, all of which have been proved to participate in meiotic spindle assembly. When oocytes were exposed to nocodazole to disassemble microtubules, Kif2a staining partly dispersed into the cytoplasm and reappeared at the inner centromeres.…”
Section: Discussionsupporting
confidence: 73%
“…This localization pattern was similar to that of the proteins involved in spindle formation, e.g. MDK28, PLK12930, Septin131, BARC132 and cep5533, all of which have been proved to participate in meiotic spindle assembly. When oocytes were exposed to nocodazole to disassemble microtubules, Kif2a staining partly dispersed into the cytoplasm and reappeared at the inner centromeres.…”
Section: Discussionsupporting
confidence: 73%
“…Immunostaining of oocytes with the anti-pS659-BubR1 antibody, which detects Cdk1-dependent phosphorylation of the KARD domain (Elowe et al, 2010;Huang et al, 2008;Kruse et al, 2013), revealed a progressive increase in the amount of phosphorylated BubR1 at the KTs throughout prometaphase and metaphase I ( Figure 4C), whereas the amount of total BubR1 at KTs showed a progressive decrease ( Figure S4A). Moreover, the amount of pT669-BubR1 in the KARD domain, which is mediated by Plk1 (Solc et al, 2015;Suijkerbuijk et al, 2012), also showed a progressive increase ( Figure S4B). Consistent with these results, the overexpression of cyclin B1, which increases Cdk1 activity (Davydenko et al, 2013), increased the amount of pS659-BubR1 ( Figure S4C) and the amount of PP2A-B56 localized to the KTs ( Figure S4D).…”
Section: Pp2a-b56 Gradually Localizes To Kts Throughout Prometaphase mentioning
confidence: 95%
“…For example, Polo-like kinase 1 (Plk1) is activated on MTOCs and is required for the localization of other centrosomal proteins to MTOCs. 28 In addition, Bora, known as a binding partner of Aurka, regulates the precise localization of Aurka and Plk1. 29 The protein expression of Bora was significantly reduced, and the levels of Plk1, phosphorylated Tpx2 also showed a decreasing tendency following Bcl2l10 RNAi (Fig.…”
Section: Bcl2l10 Rnai Reduces Mtoc-associated Protein Expressionmentioning
confidence: 99%